The contribution of plyometric exercises assisted by sensory technology on vertical jump parameters in U15 female volleyball players - Liviu Grădinaru; Petru Mergheș; Mihaela Oravițan (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. Volleyball requires high vertical jump skills for crucial actions like attacking and blocking, making jump training a focus for players, especially in youth categories. The main goal of the study was to highlight (with some specific data) the strengths and weaknesses of integrating sensory technology into the physical training program, during the entire competitive period.